Research and development of the agricultural biotechnology in Vietnam during the last twenty years (1985-2005) - Nghia, La Tuan; Quy, Tran Duy (Academia Journal of Biology, 2014)
During the last twenty years (1985-2005), the agricultural biotechnology has been rapidly developed in Vietnam and obtained significant achievements in constructing the infrastructure and in research. Vietnamese researchers have been trained at developed countries where there were the advanced laboratories with excellent experts, thus they have improved their knowledge and skill. They were playing key role in the biotechnological laboratories in Vietnam. There were several institutes/universities which were equipped with good instruments. Recently, six national key biotechnological laboratories were established where almost the experiments of the advanced biotechnology could be conducted. We have obtained results on research and application of the biotechnology in the crop breeding such as: using of the DNA markers in analysis of the gienetic diversity; mapping of the genes responsive for tolerance to the biotic and a-biotic factors; pyramiding and transfer of the useful genes into important crops; using of the cell and embryo technologies in propagation of the crops and breeds; generation of the free disease crops; crop breeding based on selection of the soma variation and mutation; created animals such as: cow, chicken, pig by applying the cell and embryo. By research and application of the microbiological technology, we have produced bio-pesticides, bio-fungicides, bio-fertilizer and bio-products used in the food production. By using of the enzyme and protein technologies, we have developed kits for detection of the poisons in crops as well as in foods, kits for rapid determination the plant and animal diseases. We have produced vaccines for the animal protection, bio-products for the produce and storage of foods and enzymes used in research an agricultural production. The agricultural biotechnology has played a very important role in the agricultural development of Vietnam.